Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

simplify (7/2-1/3) * (-2)^2 + 1/2

Sagot :

Answer:

Step-by-step explanation:

[tex]\dfrac72-\dfrac13*(-2)^2+\dfrac12=\dfrac72-\dfrac43+\dfrac12=\dfrac82-\dfrac43=\dfrac{24-8}{6}=\dfrac83[/tex]

79/6

Step-by-step explanation:

(7/2-1/3)((-2)²)+1/2

=19/6(-2)²+1/2

=19/6(4)+1/2

=38/3+1/2

=79/6

hope this helps you!

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.